2021
DOI: 10.1136/bmjopen-2021-053110
|View full text |Cite
|
Sign up to set email alerts
|

Is subjectively perceived treatment urgency of patients in emergency departments associated with self-reported health literacy and the willingness to use the GP as coordinator of treatment? Results from the multicentre, cross-sectional, observational study PiNo Bund

Abstract: ObjectivesAim of this study was to analyse if subjectively perceived treatment urgency of patients in emergency departments is associated with self-reported health literacy and the willingness to use the general practitioner (GP) as coordinator of treatment.DesignA multicentre, cross-sectional, observational study.SettingEmergency departments in five hospitals. Each hospital was visited 14 times representing two 8-hour shifts on each day of the week. Calendar dates were randomly assigned.ParticipantsAll patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
2
1
Order By: Relevance
“…An insurance claims data based analysis of the age distribution in outpatient emergency patients showed a comparable mean and variance of age as in our study [ 27 ]. However, in two studies observing patients with unselected, non-urgent conditions, the distribution of sex was more balanced than in our study [ 10 , 28 ].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…An insurance claims data based analysis of the age distribution in outpatient emergency patients showed a comparable mean and variance of age as in our study [ 27 ]. However, in two studies observing patients with unselected, non-urgent conditions, the distribution of sex was more balanced than in our study [ 10 , 28 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Grouped into three categories, 50% of our population had sufficient, 32.8% had problematic, and 17.0% had inadequate health literacy. The rates of problematic and inadequate health literacy were higher than in the general population [44], but comparable to another study in the non-urgent emergency department setting [28]. We observed that a lower health literacy was associated with reduced patient satisfaction.…”
Section: Fig 3 Patient Satisfactionsupporting
confidence: 78%
“…We conducted a retrospective, cross-sectional observational study based on personal standardized interviews in the Central Emergency Clinic of the University Medical Center Hamburg-Eppendorf. The study was part of the “PiNo” studies [15] , [16] , which were approved by the Ethics Committee of the Hamburg Medical Association on 22 July 2015 and amended on 7 March 2017 and 30 December 2019 (approval no. PV4993).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the “PiNo” studies was to characterize patients attending emergency departments, who do not require urgent treatment, with respect to their sociodemographic features, health status, and reasons for attending an emergency department. Cross-sectional observational data was collected in different hospitals as part of the “PiNo” studies [15] , [16] .…”
Section: Methodsmentioning
confidence: 99%